Doppler-tolerant receiver for an ultrasonic LPS based on Kasami sequences - Alvarez, Fernando J. (2013)
This paper presents the design of a novel receiver for a broadband ultrasonic Local Positioning System. As other devices based on matched ltering of the transmitted encoded signals, this receiver features high robustness to noise and multiple access capability. Unlike these previous solutions, the proposed receiver is capable to detect the beacons emissions despite being installed in a fast moving user and to provide an estimation of its velocity. This system has been implemented on a FPGA based architecture. An experimental analysis of the sensor performance has been carried out with a set of test signals synthetically generated to simulate diferent positions and velocities for this receiver. The results confirm the capability of the system to detect the encoded signals emitted by the LPS architecture when moving at velocities of up to 3 m/s under low SNR conditions.